Social and ideological representativeness: A comparison of political party members and supporters in Finland after the realignment of major parties - Aki Koivula; Ilkka Koiranen; Arttu Saarinen; Teo Keipi (SAGE journals, 2025)
This study provides a new frame of reference for understanding intraparty dynamics by analyzing party members' representativeness with respect to party supporters regarding socioeconomic status and ideological spectrum in a multiparty system, namely that of Finland. The analysis is based on a unique member-based survey of Finland's six major political parties (N ¼ 12,427), which is combined with supporter data derived from a nationally representative survey (N ¼ 1648). The clearest difference was found between supporters' and members' social status as members were generally in clearly higher social positions. However, there is a wider gap between parties when comparing supporters than members in terms of social status. Findings showed that political opinions on income equality is still a key difference between traditional mass parties at the different levels of party stratum, while incongruence within parties was relatively low. In contrast to the traditional parties, the newer parties, namely the Finns and the Greens, are ideologically close to their supporters in terms of attitudes concerning immigration and environment. Together, these findings provide an interesting landscape of the last decade's changes in the Finnish political spectrum and contribute to the ongoing discussion on the changing forms of political parties.